Review Article On The Role Of AI In Healthcare - Naga Kishore, R.; Sree Reddy, B. Sai; Amulya, R.; Sravani, N. (Journal of Neonatal Surgery, 2025)
Artificial Intelligence (AI) is swiftly revolutionizing the healthcare sector, providing novel solutions to enhance diagnostics, treatment, and patient care. This article examines the diverse functions of AI in healthcare, starting with its historical development and contemporary uses, such as diagnostics and imaging, personalized medicine, drug discovery, remote patient monitoring, and administrative efficiency. The advantages of AI are significant, including increased precision, economic efficiency, improved patient outcomes, and enhanced accessibility to healthcare. Incorporating AI poses challenges, including data privacy issues, algorithmic bias, regulatory obstacles, and ethical dilemmas in decision-making. Practical instances, including IBM Watson for Oncology and the use of AI in pandemic response, demonstrate its potential and influence. Future developments in explainable AI, preventive care, and genomics are poised to transform healthcare further. Notwithstanding the hurdles, AI possesses the capacity to establish a more efficient, egalitarian, and patient-centered healthcare system. This paper finishes by underscoring the necessity for continuous collaboration, regulation, and innovation to harness AI's disruptive potential in healthcare effectively.